Development of microsatellite markers for buffalograss (Buchloë dactyloides; Poaceae), a drought‐tolerant turfgrass alternative1. (3rd August 2016) - Hadle, Jacob J.; Konrade, Lauren A.; Beasley, Rochelle R.; Lance, Stacey L.; Jones, Kenneth L.; Beck, James B.
Abstract : Premise of the study: Buchloë dactyloides (Poaceae) is an important component of Great Plains prairies and a popular drought‐tolerant turfgrass alternative in North America. This species comprises an autopolyploid series, and microsatellite primers were developed to understand the distribution of genetic variation among cytotypes and across its large geographic range. Methods and Results: Fifteen microsatellite loci were designed and successfully amplified in six B. dactyloides populations. Within‐population genetic diversity was comparatively high, consistent with B. dactyloides ' life history. Allelic variation at 13 loci was consistent with the cytotype established in chromosome‐counted samples. Conclusions: This variable, interpretable set of loci allows for the determination of multilocus genotype in B. dactyloides individuals of varying cytotype. Data such as these from a range‐wide sample set can provide important insights for germplasm conservation and crop improvement in this ecologically and economically important species.